2022
DOI: 10.3390/antibiotics11081051
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolomic Analysis of a Fusidic Acid-Selected fusA Mutant of Staphylococcus aureus

Abstract: Physiological experimentation, transcriptomics, and metabolomics were engaged to compare a fusidic acid-resistant Staphylococcus aureus mutant SH10001st-2 to its parent strain SH1000. SH10001st-2 harbored a mutation (H457Y) in the gene fusA which encodes the fusidic acid target, elongation factor G, as well as mutations in a putative phage gene of unknown function. SH10001st-2 grew slower than SH1000 at three temperatures and had reduced coagulase activity, two indicators of the fitness penalty reported for fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Acid-evolved fusA mutants are fusidate-sensitive at pH 7.0. In our acid-evolved clones, the gene that showed the most mutations encodes elongation factor G (fusA), an essential translation protein associated with virulence and biofilm formation (44)(45)(46). The ancestral strain OG1RF is resistant to fusidic acid, associated with the fusA mutation C316A (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acid-evolved fusA mutants are fusidate-sensitive at pH 7.0. In our acid-evolved clones, the gene that showed the most mutations encodes elongation factor G (fusA), an essential translation protein associated with virulence and biofilm formation (44)(45)(46). The ancestral strain OG1RF is resistant to fusidic acid, associated with the fusA mutation C316A (2).…”
Section: Resultsmentioning
confidence: 99%
“…We find that experimental evolution yields pH-adaptative mutations in a number of genes, notably those encoding elongation factor G ( fusA ) at low pH and the phosphate ABC transporter ( pstABC ) at high pH. Mutations in fusA may confer resistance to fusidic acid (35, 36); but our fusA mutants show a tradeoff of fusidate sensitivity. The pts loci are associated with virulence (37, 38).…”
Section: Introductionmentioning
confidence: 93%
“…Of note, a recent study reported the transcriptional response of an in vitro -evolved fusidic acid-resistant strain derived from S. aureus SH1000. 51 This strain carried mutations in the fus A gene, which encodes EF-G and a putative phage gene. The transcriptional analysis highlighted several significant findings.…”
Section: Discussionmentioning
confidence: 99%